Professional Augmented Reality Browsers for Smartphones: Programming for junaio, Layar and Wikitude - Madden, Lester (Wiley, 2011)
Create amazing mobile augmented reality apps with junaio, Layar, and Wikitude! Professional Augmented Reality Browsers for Smartphones guides you through creating your own augmented reality apps for the iPhone, Android, Symbian, and bada platforms, featuring fully workable and downloadable source code. You will learn important techniques through hands-on applications, and you will build on those skills as the book progresses. Professional Augmented Reality Browsers for Smartphones: * Describes how to use the latitude/longitude coordinate system to build location-aware solutions and tells where to get POIs for your own augmented reality applications * Details the leading augmented reality platforms and highlights the best applications * Covers development for the leading augmented reality browser platforms: Wikitude, Layar, and junaio * Shows how to build cross-platform location-aware content (Android, iPhone, Symbian, and bada) to display POIs directly in camera view * Includes tutorials for building 2D and 3D content, storing content in databases, and triggering actions when users reach specific locations wrox.com Programmer Forums Join our Programmer to Programmer forums to ask and answer programming questions about this book, join discussions on the hottest topics in the industry, and connect with fellow programmers from around the world. Code Downloads Take advantage of free code samples from this book, as well as code samples from hundreds of other books, all ready to use. Read More Find articles, ebooks, sample chapters, and tables of contents for hundreds of books, and more reference resources on programming topics that matter to you. Wrox Professional guides are planned and written by working programmers to meet the real-world needs of programmers, developers, and IT professionals. Focused and relevant, they address the issues technology professionals face every day. They provide examples, practical solutions, and expert education in new technologies, all designed to help programmers do a better job.